2013
DOI: 10.1002/ggge.20176
|View full text |Cite
|
Sign up to set email alerts
|

Sediment‐enriched adakitic magmas from the Daisen volcanic field, Southwest Japan

Abstract: [1] The Quaternary Southwest Japan Arc is a product of subduction of the hot, young Philippine Sea Plate beneath the Eurasian Continental Plate. The magmas erupted from the Southwest Japan Arc belong to a category of magmas commonly referred to as ''adakites'' or ''adakitic magmas''. These magmas show trace element evidence for interaction with garnet at depth, and may be associated with partial melting of subducted altered oceanic crust. Also found throughout the southern Sea of Japan region are alkali basalt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
86
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(95 citation statements)
references
References 92 publications
(169 reference statements)
7
86
2
Order By: Relevance
“…This conclusion differs from that of an earlier study by Feineman et al . [], who advocated only a minimal crustal effect and concluded that the Pb isotope array for Daisen ADK can be attributed to partial melting of the subducting slab with a significant amount of sediment. The Pb isotope trends for Daisen ADK presented in these two studies are clearly different (Figure ) and Kimura et al .…”
Section: Introductionsupporting
confidence: 90%
See 3 more Smart Citations
“…This conclusion differs from that of an earlier study by Feineman et al . [], who advocated only a minimal crustal effect and concluded that the Pb isotope array for Daisen ADK can be attributed to partial melting of the subducting slab with a significant amount of sediment. The Pb isotope trends for Daisen ADK presented in these two studies are clearly different (Figure ) and Kimura et al .…”
Section: Introductionsupporting
confidence: 90%
“…(c and d) Comparison of data sets for Daisen ADK. Compositions of upper crustal (UC) [ Feineman et al ., ] and lower crustal (LC) [ Moriyama , ] lithologies are shown in the insets. The “X” indicates the hypothetical crustal component suggested by Kimura et al .…”
Section: Introductioncontrasting
confidence: 53%
See 2 more Smart Citations
“…Many models have been proposed for magma genesis in the SW Japan arc. The models include an enriched lithospheric mantle origin of OIB [ Hoang and Uto , ; Kakubuchi et al ., ], aqueous fluid‐fluxed mantle melting for AB [ Iwamori , ], carbonaceous melt‐fluxed melting for Miocene OIB [ Tatsumi et al ., ], hydrous shallow mantle melting with residual phlogopite for SHO [ Tatsumi and Koyaguchi , ], slab melt‐fluxed mantle melting for HMA [ Kimura et al ., ; Shimoda et al ., ; Tatsumi and Hanyu , ], slab melting for ADK [ Feineman et al ., ; Kimura et al ., ; Morris , ], remelting of solidified andesite for ADK [ Tamura et al ., ], and deep garnet fractionation of hydrous basalt for ADK [ Zellmer et al ., ].…”
Section: Introductionmentioning
confidence: 99%